Breeding report of a mid-late ripening white peach cultivar Shufeng - SU Mingshen; YE Zhengwen; ZHANG Minghao; LI Xiongwei; ZHANG Xianan; DU Jihong; ZHOU Huijuan; HU Yang (Guoshu xuebao)
The cultivation area and total production of peach (Prunus persica L.) in China ranked the first in the world in the past year. Shufeng was a mid-late ripening white peach cultivar derived from the cross between Jinxiu (Baihua×Yunshu No.1) as the female and Hujingmilu as the male in 2000. These seedlings were planted at the Fruit Experimental Field of Shanghai Academy of Agricultural Sciences in March of 2002, and a seedling numbered Hutao 333 was initially chosen as an excellent individual tree in 2007 based on evaluation of fruit quality and yield from 2004 to 2007. Hutao333 was tested at Zhuanghang of Fengxian and Huinan of Pudong in 2017, and at Lühua of Chongming in 2018 for regional adaptability. It was finally named as Shufeng and granted the new variety certification by Shanghai forest variety validation in 2023. The tree is moderately vigorous with high budbreak rate and branching ability, and the color of new branches varies from green to dark-red depending on age and position. Floral bud is well formed, and at an average number density of 56.08 per meter on a flower branch, which is average 2.69 cm in internode length and 4.94 mm in diameter during dormancy period. The green leaves are long elliptic-lanceolate with average 16.92 cm in length and 3.93 cm in width, and the petiole length is 1.01 cm. The flowers are rose-shaped with five sepals and petals. The pollen is fertile with high self-pollination. The fruit is about round in shape with two symmetrical halves, and has round flat to slight concave top with obvious suture line. Peel has white background covered about 25% red blush on the surface, and the density of hairs is medium. The average fruit weighed 207.76 g at three sites from 2019 to 2024, and the largest fruit reached to 428 g. The flesh is white with compact texture and medium to high juice, and covered with moderate red anthocyanin around the clingstone. The eating quality is excellent, and average soluble solids content and flesh firmness are 13.7% and 11.35 kg·cm-2, respectively. In Shanghai area, the blooming date ranged from Mar.21 to Mar.29 and the fruit ripened from July 26 to August 3, which was 14-15 d later than Hujingmilu during 2019—2024. Storage capacity of the fruit is moderate with approximate storage period of 7 days at room temperature or 20 days at 0℃. Open system with three scaffold limbs or Y shape could be adopted, and once winter pruning and twice summer pruning are recommended to balance the tree vigor. The pollination trees are not necessary, and the fruit setting rate by self-pollination is moderate. In production, fruit thinning is necessary to maintain commercial quality, and it is suitable to maintain the yield at the level of 1200-1500 kg per 666.7 m-2. Resistance to pests and diseases is generally moderate, and fruit bagging is recommended after thinning to protect unripe fruit from pests and diseases. Fertilizer, water and agricultural chemical should be applied according to requirements for tree growth and fruit development. Shufeng could be planted in suburban districts of Shanghai and similar climate areas.